Peptídeo ligante da proteína neurotoxina derivada de eosinófilos e suas aplicações no diagnóstico da esofagite eosinofílica - Narciso, Andreia Santos (2018)
Introduction: Eosinophilic esophagitis (EoE) is a chronic, allergic and inflammatory disease characterized clinically by esophageal dysfunction and fibrosis, and histologically by an increase in the number of eosinophilic infiltrates in the esophagus epithelium. Its main symptoms are dysphagia and chest pain and the main challenge of science today is the definition of a safe diagnosis for the disease. Thus, clarification of these questions lead the scientific efforts to molecular levels with the aim of obtaining diagnostic markers and prognosis for the disease, which are not yet available. Objectives: To select peptides through the molecular technique of Phage- display that can be used as EoE biomarkers. Material and methods: Firstly, comparative proteomic analyzes were performed using liquid chromatography - mass spectrometry in oesophageal biopsies of pediatric patients with EoE, gastroesophageal reflux disease (GERD) and control group. Next, the Phage-Display technology was used to select peptides against the protein identified as one of the most regulated in patients with EEo. The reactivity of the selected phage was assessed by phage-ELISA using a commercial recombinant human protein. In addition, the peptide sequences were determined by DNA sequencing and binding of the peptides to their protein target was analyzed by in silico prediction tools. Results: Mass spectrometry results showed that the eosinophil-derived neurotoxin protein (EDN), an eosinophil granule protein that is deposited in diseased tissues, was highly regulated in patients with EEo. Through phage-ELISA assays, two peptides highly reactive to EDN binding (D3 and C5) showed similar and even greater reactivity when compared with commercial polyclonal antibodies to EDN. Conclusion: The study demonstrated that the peptides selected by Phage-display detected the EDN recombinant protein and, therefore, they can be an important diagnostic tool for the detection of patients with EEo.